Snake pet ownership in the city: A case study in Greater Jakarta, Indonesia - Mirza Kusrini; Sharon Pratiwi Palesa; Burhanuddin Masy'ud (Society for Indonesian Biodiversity, 2021)
Abstract. Kusrini MD, Palesa SP, Masy’ud B. 2021. Snake pet ownership in the city: A case study in Greater Jakarta, Java, Indonesia. Biodiversitas 22: 1790-1798. Snake pets have gained popularity all over the world, including in Indonesia. We conducted an online survey to gather information regarding the characteristics of snake owners, their motivation for keeping snakes, the species owned, and the keepers’ knowledge and perception. Google forms were sent to snake owners in the Greater Jakarta area (also known as Jabodetabek), and 69 snake owners responded. Most of the snake owners are in the young adult group (16-25 years) and their motivation to keep snakes comes mostly from them being influenced by their peers, exhibitions and social media. Thirty-nine species of snake from nine families were listed as pets, mostly being snakes that are distributed in Indonesia. Overall, the Pythonidae was the snake family with the most species being selected as pets (65.7%), followed by Colubridae (10.7%) and Viperidae (9.44%). Most snake owners kept non-venomous snakes (83.3%), 12% kept highly venomous snakes, and 4.7% kept mildly- venomous snakes.  Most of the keepers had heard about protected species (91.2%). However, when asked to write the names of any protected species, 46% out of 50 people gave incorrect names. The relatively high number of venomous snakes kept (even by those keepers of a young age) indicates the potential risk of envenomation. As yet, there is no system for snake owner licensing in Indonesia, thus it is suggested that, because of the increasing popularity of keeping snakes as pets,  owners should be registered, licensed, and monitored.